2021
DOI: 10.1037/pla0000147
|View full text |Cite
|
Sign up to set email alerts
|

Playing to heal: The impact of bereavement camp for children with grief.

Abstract: Child bereavement is a difficult topic to explore and study because of stigmas in discussing death, and because of restrictions in doing research with young children. Thus, research in childhood bereavement is limited. This study focused on children who attended a bereavement camp after the traumatic loss of a loved one. The purpose was to understand the participants' grief experiences. This research study used phenomenological inquiry and analysis methodology. Five female participants were interviewed for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Play behaviors in grieving children can span the continuum; however, are frequently connected to the painful experience of loss and the coinciding need for nurturance , rescue , and repair . For example, Salinas (2021) reported similar grief-related play behaviors in her study on children who attended a bereavement camp after experiencing a traumatic loss of a loved one. Furthermore, her findings suggested that “play had a significant impact on children’s ability to cope with their losses and process their grief” (p. 46).…”
Section: Play Therapy For Grieving Military Familiesmentioning
confidence: 83%
See 1 more Smart Citation
“…Play behaviors in grieving children can span the continuum; however, are frequently connected to the painful experience of loss and the coinciding need for nurturance , rescue , and repair . For example, Salinas (2021) reported similar grief-related play behaviors in her study on children who attended a bereavement camp after experiencing a traumatic loss of a loved one. Furthermore, her findings suggested that “play had a significant impact on children’s ability to cope with their losses and process their grief” (p. 46).…”
Section: Play Therapy For Grieving Military Familiesmentioning
confidence: 83%
“…Existing literature supports play therapy for grieving children (Gonzalez & Bell, 2016; Salinas, 2021; Turner, 2020), however, there is a paucity of literature that specifically addresses grieving children in military families. Without evidence, clinicians must rely on related literature connected to grief and the experiences of military families.…”
Section: Play Therapy For Grieving Military Familiesmentioning
confidence: 99%
“…Sand therapy has long been regarded as an intervention that assists the client with processing many experiences, including grief and loss. It provides therapeutic distance to upsetting or traumatic memories (Salinas, 2021). "The tactile, nonverbal experience promotes awareness of deeply personal emotional issues within a safe, therapeutic environment" (Webber & Mascari, 2008, p. 1).…”
Section: Sand Therapymentioning
confidence: 99%
“…Some camps involve a surviving parent, though most focus exclusively on the child. [73][74][75][76] Relevant research is largely focused on short-term indicators of psychological and social well-being rather than broader and downstream metrics of more interest to policymakers but offer meaningful insight into that limited set of outcomes. Camps enable children to better articulate their feelings of loss and grief and think of their feelings as "normal."…”
Section: Grief Campsmentioning
confidence: 99%
“…In others, the child exhibited significant mental health concerns prior to program enrollment, and the parent had hoped that the camp would address this higher-level problem. 76…”
Section: Grief Campsmentioning
confidence: 99%